2022
DOI: 10.3390/app12041941
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Treatment Techniques for Short-Chain Perfluoroalkyl Substances

Abstract: In recent years, an increasing amount of short-chain perfluoroalkyl substance (PFAS) alternatives has been used in industrial and commercial products. However, short-chain PFASs remain persistent, potentially toxic, and extremely mobile, posing potential threats to human health because of their widespread pollution and accumulation in the water cycle. This study systematically summarized the removal effect, operation conditions, treating time, and removal mechanism of various low carbon treatment techniques fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…For decades, per- and polyfluoroalkyl substances (PFAS) chemicals have been widely used in various consumer, medical, and industrial products. Owing to environmental persistence and being notoriously hazardous, the long-chain PFAS chemicalsperfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS)have been prohibited under international regulations. , However, many short-chain fluorinated alternatives remain in use, and they could also be accumulated via physicochemical degradation pathways of longer-chain PFAS. Even though the use of hydrated electron (e aq – )-based advanced reductive technology (e aq – -ART) has recently shown to be effective to destruct both perfluoroalkyl carboxylates (PFxA, x = number of carbons comprising the hydrophobic tail) and perfluoroalkyl sulfonates (PFxS), PFxS with short fluoroalkyl chains such as PFBS (C 4 F 9 SO 3 – ) remains an exceptional case and displays very sluggish reactivity . To date, the abundance of short-chain PFAS from numerous sources has already been detected in most locations on the planet. Recent toxicological studies revealed that the potential threats to human health posed by analogs had been underestimated due to increased solubility, mobility, and inertness. Thus, their complete removal and decomposition from the aquatic environment has become an urgent concern.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, per- and polyfluoroalkyl substances (PFAS) chemicals have been widely used in various consumer, medical, and industrial products. Owing to environmental persistence and being notoriously hazardous, the long-chain PFAS chemicalsperfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS)have been prohibited under international regulations. , However, many short-chain fluorinated alternatives remain in use, and they could also be accumulated via physicochemical degradation pathways of longer-chain PFAS. Even though the use of hydrated electron (e aq – )-based advanced reductive technology (e aq – -ART) has recently shown to be effective to destruct both perfluoroalkyl carboxylates (PFxA, x = number of carbons comprising the hydrophobic tail) and perfluoroalkyl sulfonates (PFxS), PFxS with short fluoroalkyl chains such as PFBS (C 4 F 9 SO 3 – ) remains an exceptional case and displays very sluggish reactivity . To date, the abundance of short-chain PFAS from numerous sources has already been detected in most locations on the planet. Recent toxicological studies revealed that the potential threats to human health posed by analogs had been underestimated due to increased solubility, mobility, and inertness. Thus, their complete removal and decomposition from the aquatic environment has become an urgent concern.…”
Section: Introductionmentioning
confidence: 99%
“…Two key factors that control PFAS absorption are the electrostatic interactions between anionic headgroups of the PFASs with cationic amine groups on the sorbents and the hydrophobic interactions between the sorbents and the PFAS molecules. ,, The porosity, shape, and particle size of the sorbents are other parameters that affect the affinity and efficacy of adsorbents toward the PFAS molecules. ,, To find which factor impacts the PFOA removal mechanism, we first measured the contact angle to show the hydrophobicity and hydrophilicity of each COF’s surface (Figure S26, Movie S1). COF-I showed the most hydrophobic surface, while the hydroxy groups made COF-II more hydrophilic; as a result, the affinity of COF-II for the PFOA removal decreased dramatically (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Among these COFs, COF-I showed the best removal performance toward PFOA from these solutions, 36% from 10 mg L −1 and 85% from 1 mg L −1 solution within 24 h. Two key factors that control PFAS absorption are the electrostatic interactions between anionic headgroups of the PFASs with cationic amine groups on the sorbents and the hydrophobic interactions between the sorbents and the PFAS molecules. 15,16,65 The porosity, shape, and particle size of the sorbents are other parameters that affect the affinity and efficacy of adsorbents toward the PFAS molecules. 15,16,65 To find which factor impacts the PFOA removal mechanism, we first measured the contact angle to show the hydrophobicity and hydrophilicity of each COF's surface (Figure S26, Movie S1).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first paper authored by Liu et al, the persistence, toxicity, mobility, and widespread pollution of short-chain PFASs in the water cycle are discussed. The study compares how various treatment techniques, such as the adsorption, electrochemical oxidation, and photocatalytic degradation have certain removal effects on short-chain PFASs [5]. Among these techniques, adsorption proves to be the most widely applied technique for the effective removal of short-chain PFASs, suitable for a wide concentration range of pollution and aligning with low-carbon policies.…”
Section: Application Of Energy Saving and Low-carbon Technologies In ...mentioning
confidence: 99%